2020
DOI: 10.1016/j.nanoen.2020.105339
|View full text |Cite
|
Sign up to set email alerts
|

Re-usable self-poled piezoelectric/piezocatalytic films with exceptional energy harvesting and water remediation capability

Abstract: The need for sustainable technologies to address environmental pollution and energy crisis is paramount. Here we present a novel multifunctional nanocomposite, free standing film by combining piezoelectric molybdenum sulphide (MoS 2 ) nanoflower with poly vinylidene fluoride (PVDF) polymer, which can harness otherwise wasted mechanical energy for useful energy generation and/or water purification. The unique MoS 2 nanoflower morphology is exploited to render the wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
71
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(72 citation statements)
references
References 42 publications
1
71
0
Order By: Relevance
“…90,91 The group added molybdenum sulfide (MoS 2 ) to PVDF to obtain a multifunc-tional film that can be used for water remediation and energy harvesting. 92 Films of PVDF/barium titanate/cellulose nanocrystal composites (PVDF/BTO/CNC) were produced by Ram et al, who studied the effect of the mechanical properties of the films using BTO and CNC nanofillers. 93 In addition, a simple method makes it possible to obtain a pure β-phase by preparing films of PVDF and ionic liquid using a solution casting method and subsequent annealing.…”
Section: Piezoelectric Textilesmentioning
confidence: 99%
“…90,91 The group added molybdenum sulfide (MoS 2 ) to PVDF to obtain a multifunc-tional film that can be used for water remediation and energy harvesting. 92 Films of PVDF/barium titanate/cellulose nanocrystal composites (PVDF/BTO/CNC) were produced by Ram et al, who studied the effect of the mechanical properties of the films using BTO and CNC nanofillers. 93 In addition, a simple method makes it possible to obtain a pure β-phase by preparing films of PVDF and ionic liquid using a solution casting method and subsequent annealing.…”
Section: Piezoelectric Textilesmentioning
confidence: 99%
“…When the mass fraction of GeSe NSs is only 4 wt % at a pressure of 50 N cm −2 , the maximum open-circuit voltage density is 17.58 V cm −2 , the short-circuit current density is 1.14 µA cm −2 , and the power density is 9.76 µW cm −2 . Furthermore, a new multifunctional nanocomposite film was developed by integrating piezoelectric molybdenum disulfide (MoS 2 ) and PVDF polymers [71]. Wasted mechanical energy can be used to effectively generate power and purify water.…”
Section: Rare Earth Ionsmentioning
confidence: 99%
“…In addition, this PENG could perform robustly even after 45 days and 1500 bending periods. As mentioned above, Bagchi et al reported a reusable self-poled PENG based on a MoS2/PVDF film, and the piezoelectric film exhibits a stable piezocatalytic dye degradation efficiency and could be used repeatedly at least 10 times [71]. Reproduced with the permission from reference [76].…”
Section: Self-poled Pvdf-based Pengs With Long-term Stabilitymentioning
confidence: 99%
“…Water is commonly polluted by pesticides, organic dyes and biological contaminants such as bacteria, lipids, viruses, DNA, and proteins. 16 Air pollution and wastewater are both considered to pose a serious threat to human health. Therefore, it is important to deal with environmental pollution urgently.…”
Section: Introductionmentioning
confidence: 99%
“…However, although photocatalysis has shown very promising applications, there are few issues such as the low efficiency and difficult separation of catalysts, which limit its commercial application. 16,26 Recently, piezoelectric-based catalysts have attracted signicant attention due to their high charge separation efficiency. 26 Furthermore, in the presence of mechanical stress (i.e., either low frequency vibration or high frequency ultrasound vibration), piezoelectric materials (i.e., noncentrosymmetric in nature) generate a piezo-potential due to spontaneous polarization.…”
mentioning
confidence: 99%